Effect of polyaniline loading, types of surface modifiers and secondary doping process on the properties of poly (vinyl chloride) / poly (ethylene oxide) / polyaniline conductive films / \c Mohammed Izzuddeen bin Mohd Yazid. - Mohammed Izzuddeen Mohd Yazid (School of Materials Engineering, Universiti Malaysia Perlis, 2018)
The objectives of this research were ; to examine the effect of polyaniline filler loading on the properties,morphology and structure of poly (vinyl chloride)/poly (ethylene oxide)/polyaniline conductive films ; to analyze the effect of ethylene dimethacrylate (EDMA) as surface modifier on the properties, morphology and structure of poly (vinyl chloride)/poly (ethylene oxide)/polyaniline/EDMA conductive films ; to investigate the effect of naphthalene assurface modifier on the properties, morphology and structure of poly (vinyl chloride)/poly (ethylene oxide)/polyaniline/naphthalene conductive films ; to study the effect of secondary doping process with ferric chloride and the addition of crosslinking agent, poly (ethylene glycol) diglycidyl, on the properties, morphology and structure of poly (vinyl chloride)/poly (ethylene oxide)/polyaniline-FeCl3 and the properties of poly (vinyl chloride)/poly (ethylene oxide)/polyaniline-FeCl3/PEGDE conductive films, respectively ; to compare the properties, morphology and structure of all the conductive films mentioned above.